Compression Therapy Is Not Contraindicated in Diabetic Patients with Venous or Mixed Leg Ulcer - Mosti, Giovanni (J Clin Med, 2020)
The aim of this study was to investigate if compression therapy (CT) can be safely applied in diabetic patients with Venous Leg Ulcers (VLU), even when a moderate arterial impairment (defined by an Ankle-Brachial Pressure Index 0.5–0.8) occurs as in mixed leg ulcers (MLU). Materials and methods: in one of our previous publications we compared the outcomes of two groups of patients with recalcitrant leg ulcers. Seventy-one patients were affected by mixed venous and arterial impairment and 109 by isolated venous disease. Both groups were treated by tailored inelastic CT (with compression pressure <40 mm Hg in patients with MLU and >60 mm Hg in patients with VLU) and ultrasound guided foam sclerotherapy (UGFS) of the superficial incompetent veins with the reflux directed to the ulcer bed. In the present sub analysis of the same patients we compared the healing time of 107 non-diabetic patients (NDP), 69 with VLU and 38 with MLU) with the healing time of 73 diabetic patients (DP), 40 with VLU and 33 with MLU. Results: Twenty-five patients were lost at follow up. The results refer to 155 patients who completed the treatment protocol. In the VLU group median healing time was 25 weeks for NDP and 28 weeks in DP (p = 0.09). In the MLU group median healing time was 27 weeks for NDP and 29 weeks for DP (p = −0.19). Conclusions: when providing leg ulcer treatment by means of tailored compression regimen and foam sclerotherapy for superficial venous refluxes, diabetes has only a minor or no effect on the healing time of recalcitrant VLU or MLU.